Edgework : the Sociology of Risk-Taking. - Lyng, Stephen (Routledge, 2005)
This book will introduce the reader to the world of voluntary risk-taking, investigating the seductive nature of pursuing peril and teasing out boundaries between legal and criminal behavior.